Refugees welcome? Inter-group interaction and host community attitude formation. (January 2023) - Betts, Alexander; Flinder Stierna, Maria; Omata, Naohiko; Sterck, Olivier
Highlights: We examine the relationship between refugee-host interaction and host community attitudes towards refugees in East Africa. OLS regressions reveal a small positive correlation between refugee-host interactions and host community attitudes towards refugees in Uganda. With IV regressions, the correlation remains small and statistically significant with data from Kampala. It becomes insignificant with data from the Nakivale settlement. In all contexts, an important part of attitude formation appears to take place at the community level. The type of interaction, ethno-linguistic proximity, and urban vs. rural residency seem to affect attitude formation. Abstract: Building upon the literature on attitudes to immigration, which mainly focuses on Europe and North America, this article explores the role of inter-group interaction in influencing host community attitudes towards refugees in East Africa. It draws upon first-hand quantitative (n = 16, 608) and qualitative data collected from refugees and nearby host communities in urban and camp-like contexts in Uganda, Kenya, and Ethiopia. Focusing on the Uganda data, for which host community attitude and interaction data is available, OLS regressions reveal a small positive and significant correlation between refugee-host interaction and the perception of hosts towards refugees. This association disappears when an instrumental variable (IV) approach is used to address endogeneity issues, except when only data from the urban context is used. Combining cross-country data and qualitative data, we highlight some conditions that may shape hosts' attitudes towards refugees, including the types of interaction, ethno-linguistic proximity, and residence in urban or camp-like contexts. In all contexts, an important part of attitude formation appears to take place at the intra-group level, within households and immediate neighbourhoods, independently of individual interaction with the out-group.